Adapting to climate change and implementing mitigation measures - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Farmers in Nicaragua, supported by CIAT, are transforming from traditional crops to systems more adapted to climate change showing various examples of ecological agriculture, such as soil recovery, crop diversification and water harvest systems to face water scarcity problems in the dry period, in order to take advantage of land in a more intensive way. Photos: J.L. Urrea (CCAFS)